2014
DOI: 10.1177/0306396814542923
|View full text |Cite
|
Sign up to set email alerts
|

Asylum seekers’ Occupy movement in Hong Kong

Abstract: This piece offers preliminary reflections on the theoretical justification of a highly organised protest staged against the non-profit organisation contracted by the Hong Kong Government to provide asylum seekers with humanitarian assistance. In so doing, it reveals the central role played by asylum seekers reacting to border policies and practices that cause their immiseration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The latest wave of refugee surge started in the 2000s – this time the refugees or asylum seekers come mainly from war-torn countries in Africa, such as Somalia, and from South Asian countries, such as Pakistan, Bangladesh and Sri Lanka (Shum, 2014). Unlike previous inflows, the recent arrivals are racially and ethnically diverse and they came to Hong Kong both by air and by boat (Shum, 2014; Vecchio and Beatson, 2014). Excluding irregular migrants, the magnitude of the flow is much more moderate, numbering in the thousands or tens of thousands.…”
Section: The Hong Kong Refugee Context and Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The latest wave of refugee surge started in the 2000s – this time the refugees or asylum seekers come mainly from war-torn countries in Africa, such as Somalia, and from South Asian countries, such as Pakistan, Bangladesh and Sri Lanka (Shum, 2014). Unlike previous inflows, the recent arrivals are racially and ethnically diverse and they came to Hong Kong both by air and by boat (Shum, 2014; Vecchio and Beatson, 2014). Excluding irregular migrants, the magnitude of the flow is much more moderate, numbering in the thousands or tens of thousands.…”
Section: The Hong Kong Refugee Context and Theoretical Frameworkmentioning
confidence: 99%
“…Refugee groups alleged that the system of subcontracting food rationing to specific food stores invited corruption and abuse. The amount and quality of food rations had been reduced despite an increased budget allocated to the ISS-HK by the Hong Kong government; refugees said that they often received only sub-standard or rotten food (Vecchio and Beatson, 2014).…”
Section: Local Policy Context and Refugee Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…This research study is vital since by now because existing studies fail to review refugee policies in Hong Kong comprehensively. It is observed that most of the existing refugee studies in Hong Kong are concentrated on the legal perspective (Jones, 2009; Lau, 2017; Loper, 2010; Ramsden, 2013; Ramsden and Marsh, 2013, 2014), the lived experiences of refugees (Lau and Gheorghiu, 2018; Mathews et al , 2014; Shum, 2019; Vecchio, 2016), the roles of non-governmental organizations (NGOs) and refugee community organizations (Lau, 2019; Vecchlo and Beatson, 2014) and the health caring perspective (Wong et al , 2016). Although there is a small body of studies examine the relationship between the formation of refugee policies and media frames (Ng et al , 2019) and the effectiveness of related policies (Ng, 2019), the present study evaluates the securitization process of refugees in terms of a longer time frame.…”
Section: Introductionmentioning
confidence: 99%